Towards a new scenary for research assessment: the institutional repository (AIR) of Milan University - Paola Galimberti (JLIS.it, 2010)
The aim of this work is to report about the unconventional use of an institutional repository, that has been used as data source to assess the scientific production and productivity within the Departments of the Faculty of Letters at the University of Milan.